Promoting viability of 3D-bioprinted adipose tissue - Hilmersson, Hugo (My University, 2026)
Bioprinting is a promising technique for soft tissue reconstruction and enables custom design of autologous tissue that could replace lost tissue, restore function and reduce the need for donor tissues. Ensuring survival and nutrient supply to the tissue remains a major challenge. Due to ethical reasons, methods to study viability and vascularization in vitro needs to be developed. This thesis aims to evaluate methods to study viability of bioprinted adipose tissue in vitro. The second aim is to assess if addition of adipose derived human stromal vascular fraction (SVF) to 3D- bioprinted tissues promotes adipocyte viability in vitro. Microfragmented, human adipose tissue combined with an oxidized nanofibrillated cellulose hydrogel and alginate solution was bioprinted and stabilized through cross-linking using CaCl2. SVF was cultured and added to the bioink pre- and post- printing. Viability was measured with a metabolic assay, alamar Blue, combined with fluorescence assays and histology during culture in vitro for 14 days. Efforts to create a model where SVF could be concentrated were done by evaluation of potential sacrificial inks. The results showed an almost linear trend between adipose tissue content and reduction of the alamar Blue reagent. Printed adipose tissue without SVF could be determined dead after three days in vitro. Furthermore, the assay indicated that infusing and covering bioprinted adipose tissue with SVF could promote viability for 14 days in vitro with a constant 20 % reduction. The majority of the sacrificial inks exhibited low viscosity, clumping or problems when extruded. However, combining porous gelatine microcarriers with an equal amount of cellulose hydrogel or gelatine produced a network with adequate fidelity. Conclusions were that alamar Blue assay can be used to measure viability of bioprinted adipose tissue. Moreover, addition of SVF in and on the bioprinted construct can promote viability of the adipose tissue. Finally, more research is needed to combine these findings with sacrificial inks to promote vascularization. This thesis provide a foundation for future research in creating and promoting vascular networks in bioprinted tissue used for reconstruction surgery.
Keywords: Bioprinting; nanofibrillated cellulose; microfragmented adipose tissue; stromal vascular fraction; adipocyte viability; vascularization